Cushioning material for glass plate and glass laminate
A cellulose-based buffer material with a coating layer addresses environmental concerns and functional requirements for glass plate stacking by being biodegradable and providing necessary strength and adhesion.
Patent Information
- Application Number
- JP2024124943
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-15
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The use of synthetic resin powders as buffer materials between stacked glass plates poses environmental concerns due to potential release into the environment and adverse effects on wildlife, while also requiring high functionality to prevent scratches and surface deterioration.
A buffer material composed of cellulose particles with a coating layer, containing 50% or more cellulose by weight, and optionally including organic acid particles and water-soluble inorganic salts, which are biodegradable and provide the necessary strength and adhesion for glass plate stacking.
The cellulose-based buffer material effectively reduces environmental impact by being biodegradable, while maintaining the required properties for protecting glass plates during stacking, transportation, and processing.
Smart Images

Figure 2025043271000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a buffer material for placement between stacked glass sheets. [Background technology]
[0002] When glass plates are transported, stored, or handled, buffer materials are inserted between each of the stacked glass plates to prevent scratches caused by contact between the glass plates and deterioration of the glass surface called blue and white tarnish. There is a technology that uses powder made of synthetic resin particles (beads) with particle diameters of several tens to several hundreds of μm as the buffer material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] U.S. Patent No. 10,611,546 Summary of the Invention [Problem to be solved by the invention]
[0004] There are concerns about the impact of the powder used as the buffer material on the environment. For example, when the powder is spread on the surface of a glass plate, the powder falls from the surface of the glass plate. The powder that falls from the glass plate is collected, but there is no guarantee that it is complete, and there is a risk that it will be released into the environment (for example, mixed with cleaning water and flowing into the sewer). In addition, the powder is removed from the surface of the glass plate during secondary processing of the glass plate (cutting or processing for commercialization), and the same risk exists at this time. In addition, although the amount is small, there is a possibility that the powder will scatter during transportation or transportation in the manufacturing process of the glass plate laminated via the powder.
[0005] From the viewpoint of protecting the natural environment, it is undesirable for synthetic resin powder to be released into the environment. For example, there are concerns about the adverse effects of the accumulation of synthetic resin powder on fish, shellfish, birds, and animals.
[0006] On the other hand, the glass plates are required to have a high level of surface properties (flatness, absence of scratches and dirt), and in order to reliably protect the stacked glass plates during transportation, the powder held between the glass plates is also required to have high functionality (strength and retention).
[0007] In this context, the present invention aims to provide a buffer material to be held between stacked glass sheets, which has a reduced impact on the natural environment and has the functions required for holding the stacked glass sheets together. [Means for solving the problem]
[0008] The present invention relates to a buffer material for glass plates to be interposed between glass plates, the buffer material being a powder containing cellulose particles having a coating layer formed thereon, the powder containing 50% by weight or more of a cellulose component. The present invention also relates to a buffer material for glass plates to be interposed between glass plates, the buffer material being a powder containing cellulose particles, the powder containing 50% by weight or more of a cellulose component. In one embodiment of the present invention, the cellulose particles are granulated viscose. In one embodiment of the present invention, the powder contains organic acid particles having an average particle size smaller than the average particle size of the cellulose particles.
[0009] In the present invention, the organic acid may be one or more selected from adipic acid, succinic acid, and citric acid. In the present invention, the cellulose particles may have an average particle size of 10 μm to 200 μm, and the organic acid particles may have an average particle size of 5 μm to 50 μm. It is also possible to incorporate the organic acid into the powder by dissolving the organic acid in an aqueous solution and coating the cellulose particles with the aqueous solution.
[0010] In the present invention, the powder may contain, as an additive, particles of a material whose average particle size is smaller than that of the cellulose particles and whose position in the triboelectric series is on the lower potential side than the cellulose particles. In the present invention, the additive may be particles of a material whose position in the triboelectric series is in the negative region. In the present invention, the cellulose particles may have a moisture content of 1% by weight or less.
[0011] In the present invention, the powder may contain water-soluble inorganic salts. Here, examples of the water-soluble inorganic salts include sodium sulfate (Na2SO4), sodium nitrate (NaNO3), sodium carbonate (Na2CO3), sodium chloride (NaCl), potassium chloride (KCl), sodium hydroxide (NaOH), sodium tetraborate (Na2B4O710H2O), sodium tripolyphosphate (Na5P3O 10 In the present invention, the powder may contain sodium acetate.
[0012] In the present invention, the cellulose particles may be covered with a coating layer having biodegradability. In the present invention, the coating layer may be a layer of a water-soluble high molecular weight organic polymer. In the present invention, the coating layer may be a layer of water-soluble cellulose. In the present invention, the cellulose particles may be covered with a coating layer containing a water-soluble inorganic salt. In the present invention, the cellulose particles may be covered with a coating layer containing an organic acid. Effect of the Invention
[0013] The cellulose particles are biodegradable and decompose in the natural environment. Therefore, the impact on the natural environment is reduced. Furthermore, the cellulose particles have the properties required for a buffer material held between stacked glass sheets. Therefore, a technology is obtained that provides a buffer material held between stacked glass sheets that has a reduced impact on the natural environment and has the properties required for holding the stacked glass sheets. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a conceptual diagram of an embodiment. [Diagram 2] 1 is a graph showing particle size distribution. [Diagram 3] 1 is a graph showing charging characteristics. [Figure 4] 1 is a graph showing the change in weight of a sample in a measurement for investigating moisture adsorption. [Diagram 5] Photographs (A), (B), and (C) are used as substitutes for drawings, showing the state of adhesion to glass when adipic acid powder is added to cellulose powder. [Figure 6] Photographs (A), (B), and (C) are used in place of drawings to show the state of adhesion of cellulose particles to a glass bottle. [Figure 7] FIG. 2 is an image showing the cross-sectional structure of a cellulose particle covered with a coating layer. [Figure 8] FIG. 1 is an image diagram showing a method for measuring adhesion of particles to a glass plate. [Figure 9] 1 is a graph showing the measurement results of adhesion of cellulose particles to a glass plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] (overview) 1 shows a state in which four glass plates 101, 102, 103, and 104 are stacked. The number of glass plates to be stacked is not limited, but four plates are shown here as an example. The applications of the glass plates are not limited, but examples include those for architecture, vehicles, displays, and solar cells.
[0016] A powder layer 111 is provided between the glass plates 101 and 102, a powder layer 112 is provided between the glass plates 102 and 103, and a powder layer 113 is provided between the glass plates 103 and 104. The powder layer 111 functions as a buffer layer that prevents the glass plates 101 and 102 from coming into direct contact with each other. The powder layers 112 to 113 also have this function. In addition, the powder layers 111 to 113 have the function of holding the vertically adjacent glass plates so that they do not move relative to each other due to vibration or impact, and the function of absorbing vibration and impact.
[0017] The powder layers 111-113 are composed of spherical cellulose (cellulose particles) powder with an average particle size of 10 μm-400 μm, preferably 50 μm-150 μm or 100 μm-200 μm, and additive powder. Note that the term "particle" refers to individual grains.
[0018] The thickness of the powder layers 111-113 is about 10 μm to 400 μm, preferably about 100 μm to 200 μm or about 50 μm to 150 μm. When sandwiched between glass plates, the weight of the glass plates may cause the cellulose particles to deform, and the outer diameter of the cellulose particles may become as small as about 90%. Therefore, the thickness of the powder layers 111-113 may become smaller than the maximum particle diameter (outer diameter) of the cellulose particles in a free state.
[0019] (About powder) The powder layers 111 to 113 in Fig. 1 are composed of spherical cellulose particles and additives. The cellulose particles used in this embodiment are spherical regenerated cellulose particles. These cellulose particles are manufactured by the following method using pulp as a raw material. Basically, cellulose particles are obtained by manufacturing viscose and spheronizing it.
[0020] The manufacturing process of cellulose particles will be briefly described below. First, pulp is soaked in an alkaline liquid (sodium hydroxide solution) to obtain alkali cellulose. Next, the alkali cellulose is squeezed and further pulverized. After that, the pulverized material is aged to make the degree of polymerization uniform. This is dissolved with carbon disulfide and dissolved in water to make a solution. This solution is filtered, aged, degassed, and further filtered to obtain viscose. This viscose is spheroidized by a spraying method to obtain spherical cellulose particles with an outer diameter of, for example, 100 μm to 200 μm. The particle size is controlled by controlling the conditions of the spheroidization process. In addition to the spraying method, other spheroidization methods include a dropping method and a phase separation method.
[0021] The additive is for improving the adhesion of the cellulose particles to the glass plate and for adjusting the pH of the powder layer when the alkaline component is eluted from the glass plate, and is, for example, a powder of an organic acid (adipic acid, succinic acid, citric acid, etc.). Other additives include smaller cellulose particles (average particle size of about 5 μm to 50 μm), rice flour, HPC (hydroxypropyl cellulose) particles, etc. Additives other than organic acids can also be used. This will be described later.
[0022] The main component of the powder constituting the powder layers 111 to 113 is cellulose particles. The ratio of the cellulose component in the powder constituting the powder layers 111 to 113 is preferably 50% by weight or more.
[0023] (Features) Cellulose is the main component of the cell walls of plant cells and plant fibers, and is biodegradable. Also, cellulose is a natural substance, and there is no adverse effect on the natural environment even if it is released into the natural environment. Furthermore, cellulose particles have significant properties required for a buffer material (for example, powder layers 111 to 113 in FIG. 1) held between stacked glass plates. This point will be described below.
[0024] (Measurement) Measurements were made for various powders regarding (1) adhesive strength, (2) electrostatic decay, (3) frictional properties between the powder and glass plate, (4) particle strength, and (5) moisture adsorption properties. The objects were a powder of cellulose particles of the present embodiment (Sample A), a comparative powder of polyethylene particles (Sample B), and a comparative powder of acrylic particles (Sample C). The physical properties of each sample are shown in Table 1 below. Note that FIG. 2 shows the particle size distribution of each sample used in the adhesive strength measurement.
[0025] [Table 1]
[0026] (1) Adhesion This is the force that particles have to adhere to a glass plate. The stronger the adhesive force, the stronger the adhesion to the glass. If the adhesive force is weak, the particles are more likely to come off the glass plate due to vibration, impact, wind, etc. When powder is to be held on a horizontal glass plate, a large adhesive force is not required. However, when the glass plate is not horizontal, an appropriate adhesive force is required to keep the particles attached. In particular, when powder is to be held on the surface of a standing glass plate (a vertical surface), an adhesive force strong enough to prevent the powder from falling is required.
[0027] The adhesion was measured using a centrifugal adhesion measuring device (NS-C100 model manufactured by Nano Seeds Co., Ltd.). In this measurement, the sample was attached to the surface of a substrate (glass plate), and then the substrate was centrifuged at six levels of 100G to 800G in a centrifuge, the state of particle separation was recorded as an image, and the particle residual rate after rotation was measured against the initial number of particles attached before centrifugation.
[0028] The adhesion force of a particle to the substrate is equal to the centrifugal separation force acting on the particle, F = (π / 6)ρd 3 rω 2Here, ρ is the true density of the particles, d is the particle diameter, r is the rotation radius of the centrifuge, and ω is the rotation angular velocity of the centrifuge. The particle residual rate after rotation was plotted on the horizontal axis, and the separation force of the particles at each rotation part was plotted on the vertical axis, and the average adhesion force (separation force at which 50% of the particles separate) was calculated from the exponential approximation curve.
[0029] The measured adhesive strength was 52.4 nN for sample A, 3656.4 nN for sample B, and 10670.5 nN for sample C. The cellulose particle powder (sample A) had a smaller adhesive strength than the synthetic resin particle sample.
[0030] (2) Static electricity dissipation It indicates the ability of a particle to be charged. When the charge decay rate is large, it means that the charge is easily eliminated and the chargeability is low. When the charge decay rate is small, it means that the charge is difficult to eliminate and the chargeability is high.
[0031] The charge decay was measured using a static electricity diffusion rate measuring device (NS-D100 model manufactured by Nano Seeds). The measurement conditions were a charge time of 1 second, a sampling frequency of 1 Hz, and a recording time of 600 seconds. The distance from the sensor to the powder surface was 1 mm, and the sample was charged by corona discharge, and the decay of the surface potential when it was positively charged and negatively charged was measured.
[0032] Figure 3 shows a graph of the measured decay characteristics of the particle surface potential. As shown in Figure 3, Sample A loses its charge in a short time even after being charged, compared to Sample B and Sample C. This shows that the cellulose particle powder (Sample A) has a lower chargeability than the synthetic resin particle powders Sample A and Sample B.
[0033] (3) Friction characteristics between powder and glass plate A powder bed shear test was conducted to measure the powder kinetic friction angle and compressibility of each sample powder. These physical property data are parameters that indicate the frictional characteristics of the powder. These physical property data were measured using a powder bed shear force measuring device, according to the method established in the JIS standard (JIS-Z8835). The powder bed shear force measuring device used was the "Powder Bed Shear Force Measuring Device NS-S500" manufactured by Nano Seeds Co., Ltd.
[0034] (3-1) Powder dynamic friction angle The powder kinetic friction angle is defined in JIS-Z8835 and indicates the degree of resistance to shear force between particles.
[0035] The powder layers 111 to 113 in Fig. 1 are required to have the function of firmly holding adjacent glass plates together. When a force acts to displace the stacked glass plates in parallel, a force acts to displace the powder layers in contact with the two glass plates in parallel. Powders with a large powder layer friction angle have low fluidity, and when used as the powder layer, they exert a large resistance to the force to displace the powder layer in parallel. Table 2 shows the measurement results for the powder kinetic friction angle.
[0036] [Table 2]
[0037] Table 2 shows that the cellulose particle powder (Sample A) has a larger powder kinetic friction angle and is more effective at firmly holding adjacent glass plates together than the synthetic resin particle powders Sample A and Sample B.
[0038] (3-2) Compression ratio The compression ratio is an index of the packing of the powder. Table 3 shows the compression ratio of each sample. If the initial packing of the powder is high, the compression ratio during the test is low and the contact ratio of the particles to the glass surface is high. This indicates that the particles are in uniform and dense contact with the glass surface.
[0039] Table 3 shows data indicating that the initial packing of the cellulose particle powder (sample A) is high (more densely packed). This indicates that the cellulose particle powder (sample A) is in uniform and dense contact with the glass surface (in other words, the particles are distributed more tightly on the surface of the glass plate) compared to the synthetic resin particle powders of samples B and C. This is a significant characteristic for the glass plate cushioning material of the present invention. This characteristic also indicates that there are fewer gaps between particles on the glass plate surface, and fewer particles fall off due to not being able to contact the surface of the glass plate when sprayed (these particles are wasted).
[0040] [Table 3]
[0041] (4) Particle strength The deformation strength was measured as the strength of the particles. In elastic-plastic or ductile materials, deformation often continues without breaking. Therefore, focusing on the degree of deformation, the applied force when compressively displaced by 50% of the particle diameter was measured as the deformation strength.
[0042] The measurement was carried out on 10 samples using a microparticle crushing force measuring device (NS-A300 model manufactured by Nanoseeds Co., Ltd.). In the measurement, the particles were pressed into the crushing needle, and a waveform chart of the pressing force at this time was recorded. The amount of compression was also measured from the displacement of the crushing needle.
[0043] The deformation strength is σ 10% =F 10% / A (JIS Z 8844), where σ 10% is the deformation strength (Pa) for a compressive displacement of 10% of the particle diameter. F 10% is the test force (N) for a compressive displacement of 10% of the particle diameter. A is the area (m 2 ) The particle size was measured by image analysis. Here, the deformation strength σ 50% Table 4 shows the measurement data related to the particle strength.
[0044] [Table 4]
[0045] As shown in Table 4, Sample A (cellulose particles) exhibits high particle strength. Pressure is applied to the glass plate cushioning material of the present invention when it is sandwiched between glass plates, and it is important that the particles do not break due to this pressure. Particle breakage can cause damage (scratches) to the glass surface. In this respect, Sample A (cellulose particles), which has high particle strength, is suitable for the glass plate cushioning material of the present invention.
[0046] (5) Moisture adsorption This indicates the ability to adsorb moisture. The higher the moisture adsorption value, the greater the ability to adsorb moisture. Moisture adsorption was measured by placing a sample in a thermo-hygrostat chamber at 40°C and 75% RH for 12 hours, and then at 25°C and 40% RH for another 12 hours, and measuring the change in sample weight during that time.
[0047] FIG. 4 is a graph showing the change in weight of the samples. As shown in FIG. 4, sample A shows a larger weight change than the other samples. This indicates the change in the amount of moisture contained. The weight change of sample A indicates that it contains more moisture in the first high-temperature, high-humidity environment and releases the moisture in the next low-temperature, low-humidity environment. The degree of this change is much larger in sample A than in samples B and C. This indicates that sample A is more likely to adsorb moisture than samples B and C. This characteristic is preferable in that it has the effect of reducing chemical reactions involving moisture on the glass surface by absorbing moisture from the atmosphere.
[0048] (comprehensive evaluation) The main properties required for the powder layer to be placed between the laminated glass plates are (3) the friction properties between the powder and the glass plates (see Table 2) and (4) the strength of the particles (see Table 4). As mentioned above, cellulose particles have properties that exceed those of synthetic resin particles with respect to properties (3) and (4).
[0049] In addition, cellulose particles have a higher initial packing density than synthetic resin particles, and come into uniform and intimate contact with the glass surface, which allows a highly uniform buffer layer to be formed on the surface of the glass sheet, while also reducing the generation of unnecessary particles.
[0050] (Improvement of adhesion) Incidentally, when glass sheets are packed or handled, powder may be sprinkled on the glass sheets in an upright state, and the glass sheets may then be stacked. In this case, the powder used is required to have adhesive strength.
[0051] The cellulose particles from which the data in Tables 1 to 4 were obtained are promising as a buffer material for glass plates in terms of friction and strength, but as the measurement results show, their adhesion to glass plates is weak. Therefore, additives are added to improve the adhesion of the cellulose particles to glass plates. Here, an example is described in which a powder of organic acids (adipic acid, succinic acid, citric acid, etc.) is mixed with a powder of cellulose particles with an average particle size of 100 μm to 200 μm to improve the adhesion of the powder as a whole to glass plates.
[0052] The organic acid powder used has a particle size smaller than that of the cellulose particles. The particle size of the organic acid particles attached to the cellulose particles is preferably about 0.1 μm to 50 μm, and more preferably about 5 μm to 15 μm.
[0053] The amount of organic acid added is about 0.1% by weight to 50% by weight of the total powder constituting the powder layers 111 to 113. If the amount of organic acid particle powder mixed is less than an appropriate amount, the effect of improving adhesive strength decreases. If the amount of organic acid particle powder mixed is too much, the pH balance may be lost.
[0054] Adipic acid has a high electrostatic property, and is expected to have the effect of increasing the adhesion of cellulose particles to a glass plate. FIG. 5 is a drawing substitute photograph showing the state of adhesion of a powder obtained by mixing cellulose particles of sample A in Table 1 and adipic acid particles with an average particle size of 10 μm to 30 μm to the inside of a glass bottle. FIG. 5(A) shows the case of a weight ratio of (cellulose particles: adipic acid particles = 99: 1), FIG. 5(B) shows the case of a weight ratio of (cellulose particles: adipic acid particles = 95: 5), and FIG. 5(C) shows the case of a weight ratio of (cellulose particles: adipic acid particles = 90: 10). As is clear from FIGS. 5(B) and (C), it can be seen that the addition of adipic acid particles to the powder of cellulose particles improves the adhesion to the glass surface.
[0055] From the above results, it is concluded that the adhesion of a powder whose main component is cellulose particles to a glass surface can be improved by adding 5% by weight or more, preferably 10% by weight or more (upper limit 50% by weight) of adipic acid particle powder to a powder whose main component is cellulose particles.
[0056] Organic acids are also effective in preventing glass tarnish. Glass tarnish is a phenomenon in which interference fringes appear on the surface of glass or the glass becomes cloudy. The former is called blue tarnish, and the latter is called white tarnish. Blue tarnish occurs when alkali (Na+ or Ca+) dissolves from the glass into water that comes into contact with the glass surface, forming an uneven layer on the surface of the glass that is deficient in alkali ions, and interference fringes appear due to the interference of light caused by this uneven layer. White tarnish occurs when a small amount of alkali (Na+ or Ca+) dissolves from the glass surface and dissolves in water. As the water evaporates, the concentrated alkaline solution corrodes the glass surface, and this solution further reacts with acid gases in the air, causing sodium carbonate or calcium carbonate to precipitate on the glass surface.
[0057] Since the organic acid is acidic, the alkalinization in the process of the glass tarnish generation is suppressed, and the generation of white tarnish is suppressed. Different types of organic acids can be used in combination.
[0058] Additives other than organic acids can also be used as additives to be added to the powder layer between the glass plates. Examples of additives other than organic acids include water-soluble inorganic salts. Water-soluble inorganic salts improve the adhesive strength of cellulose particles to the glass plates and have the effect of suppressing the occurrence of glass tarnish.
[0059] Water-soluble inorganic salts are water-soluble compounds that contain sodium and potassium. Examples of water-soluble inorganic salts include sodium sulfate (Na2SO4), sodium nitrate (NaNO3), sodium carbonate (Na2CO3), sodium chloride (NaCl), potassium chloride (KCl), sodium hydroxide (NaOH), sodium tetraborate (Na2B4O710H2O), and sodium tripolyphosphate (Na5P3O 10 These water-soluble inorganic salts may be used alone or in combination.
[0060] Methods for introducing water-soluble inorganic salts include (1) a method using particles of water-soluble inorganic salts, (2) a method in which water-soluble inorganic salts are dissolved in water and coated on the surfaces of cellulose particles, and (3) a method in which both methods are used in combination. A spray coating method described later can be used as a method for coating the surfaces of cellulose particles with water-soluble inorganic salts. In this case, the cellulose particles are covered with a coating layer containing the water-soluble inorganic salts. The amount of water-soluble inorganic salts added is about 0.1% by weight to 50% by weight based on the total powder constituting the powder layers 111-113.
[0061] When the powder layer between the glass plates contains water-soluble inorganic salts, alkali ions (such as Na+) are dissolved from the water-soluble inorganic salts into the moisture between the glass plates and the moisture released from the cellulose particles, and cover the surface of the glass plate. The dissolution of alkali ions (such as Na+) from inside the glass plate to the glass surface occurs due to the difference in the concentration of alkali ions inside and outside the glass plate. When the powder layer between the glass plates contains water-soluble inorganic salts, the concentration difference is corrected, so the dissolution of alkali ions from inside the glass plate to the glass plate surface is suppressed. Furthermore, the alkali content dissolved from the water-soluble inorganic salts moves to the alkali-deficient area near the glass plate surface, so the amount of alkali ions in the glass plate is stabilized, and the exchange of hydrogen ions and alkali ions in the air and cellulose powder is suppressed. As a result, the occurrence of blue tarnish is suppressed.
[0062] In addition, since the elution of alkali ions onto the glass sheet surface is suppressed, the generation of sodium carbonate or calcium carbonate on the glass surface due to the eluted alkali ions, i.e., whitening, is also suppressed. Although sodium carbonate and the like is generated due to the alkali ions eluted from the water-soluble inorganic salts mixed into the powder layer, this is not due to the alkali ions precipitated on the glass sheet surface, and even if the water-soluble inorganic salts remain on the glass surface, they have the property of being difficult to hydrogen bond with the glass surface, and are therefore easily removed by subsequent cleaning.
[0063] It is also possible to use a plurality of water-soluble inorganic salts. It is also possible to use a combination of an organic acid and a water-soluble inorganic salt. In this case, the water-soluble inorganic salts suppress the elution of alkaline components from inside the glass sheet to the surface, and the organic acid suppresses the production of sodium carbonate and calcium carbonate caused by the alkaline components. Particles of water-soluble organic salts such as sodium acetate can also be used as an additive for suppressing the occurrence of glass tarnish. The presence of these water-soluble organic salts suppresses the occurrence of glass tarnish. The amount of these additives added is the same as that of other additives.
[0064] (Embodiment 1) The powder layer to be interposed between the laminated glass plates is made of 90% by weight of cellulose particles with an average particle diameter of 100 μm and 10% by weight of adipic acid particles with an average particle diameter of 10 μm to 30 μm. The optimal outer diameter of the adipic acid particles is about 0.1 to 20 μm, and the preferred particle size distribution is about 4 μm (x10) to 80 μm (x90).
[0065] (Embodiment 2) The powder layer to be interposed between the laminated glass plates is made of 90% by weight of cellulose particles with an average particle size of 100 μm and 10% by weight of succinic acid particles with an average particle size of 10 μm to 30 μm.
[0066] (Embodiment 3) The powder layer to be interposed between the laminated glass plates is made of 90% by weight of cellulose particles with an average particle size of 100 μm and 10% by weight of citric acid particles with an average particle size of 10 μm to μm.
[0067] (Embodiment 4) The cellulose particles may be porous or fibrous. In addition, the cellulose particles may be a mixture of two or more types selected from smooth surface, porous, and fibrous cellulose particles.
[0068] (Embodiment 5) Additives that increase adhesion include particles of materials that are lower in the triboelectric series than cellulose particles. Cellulose particles are positively charged by friction, and glass is also positively charged by friction. This is thought to be one of the reasons why cellulose particles have low adhesion to glass.
[0069] Examples of particles of materials that are lower in the triboelectric series than the cellulose particles include paper and wood particles. In particular, those in the negative region of the triboelectric series (negatively charged by frictional charging) are preferable. By using particles in the negative region of the triboelectric series, the powder mainly composed of cellulose particles is negatively charged by frictional charging, and the adhesion of the cellulose particles to glass, which is positively charged, is increased. It is also possible to use particles with controlled charging properties as additives by carrying out some kind of treatment or using a charge control material.
[0070] (Embodiment 6) In this embodiment, in the process of attaching the powder of cellulose particles scattered on a glass plate to the glass plate, the powder of cellulose particles is charged to a first polarity (positive or negative). On the other hand, the surface of the glass plate is charged to a second polarity (negative or positive). Then, cellulose particles charged to the first polarity are scattered on the glass plate charged to the second polarity and attached to it. At this time, an attractive Coulomb force acts between the positive and negative charges, and the cellulose particles adhere to the glass plate with a high adhesive force. The charging is performed using an ion generating device that generates positive and negative ions by discharging.
[0071] As shown in Fig. 3, the charging time of the cellulose particles lasts for about 40 to 60 seconds, during which time the glass plates are laminated (a second glass plate is placed on a first glass plate). The charging characteristics of glass are sufficiently high compared to the cellulose particles, so no problems arise. This embodiment can be combined with other embodiments.
[0072] The cellulose particles only need to adhere to the glass plates until the plates are stacked. Once the plates are stacked, the high friction properties of the cellulose particles (see Table 2) ensure that the layer of cellulose particles is firmly held between the plates.
[0073] In this embodiment, the cellulose particles may be dried as described below. By drying, the chargeability of the cellulose particles is further increased, and the adhesion to the glass plate due to static electricity can be further increased. The additives are the same as those in the other embodiments.
[0074] (Embodiment 7) The cellulose particles may be subjected to a plasma treatment, which modifies the surface of the cellulose particles and improves their adhesion to a glass plate.
[0075] (Embodiment 8) Dried cellulose particles are used to compose the powder layers 111-113. Here, cellulose particles with a moisture content of 1% by weight or less are used. There is no particular lower limit to the moisture content, but considering the cost of the drying process and moisture absorption during use, the lower limit of the moisture content is about 0.01% by weight. By lowering the moisture content of the cellulose particles, the adhesion to the glass surface is increased.
[0076] In this case, a powder of cellulose particles that has been dried to a moisture content of 1% by weight or less is used. The drying method is not particularly limited, but for example, the powder of cellulose particles is heated. The cellulose particles after drying are stored in a sealed state so that the dry state is maintained. The additives are the same as those in the other embodiments.
[0077] Dried cellulose particles have a high electrostatic charge, so they adhere better to glass plates than non-dried cellulose particles. Dried cellulose particles also have a high water absorption capacity, so they are effective in preventing glass tarnish. As mentioned above, glass tarnish (blue tarnish and white tarnish) occurs when alkali components in the glass are dissolved by water that comes into contact with the glass surface.
[0078] Cellulose particles have high hygroscopicity, as described in FIG. 4 and the associated description. The data in FIG. 4 is for samples that have not been dried beforehand, but have been intentionally dried, and thus have even higher hygroscopicity. Thus, the dried cellulose particles function as a moisture adsorbent (hygroscopic material) between the glass plates due to their high water adsorption.
[0079] Therefore, by placing dried cellulose particles between glass plates, the presence of moisture in contact with the surface of the opposing glass plate is suppressed, and the occurrence of glass discoloration is suppressed. In other words, dried cellulose particles have the two advantages of (1) being highly electrostatically charged in a dry state, resulting in strong adhesion to the glass surface, and (2) having the effect of suppressing the occurrence of glass discoloration caused by the adsorption of moisture.
[0080] The effects obtained by drying are explained below. Table 5 shows the results of investigating the chargeability depending on the drying state of the cellulose particles of sample A in Table 1. In this experiment, the cellulose particles were charged with a positive polarity, and the glass (glass bottle) was charged with a negative polarity. Table 1 shows the charge amount (nC), weight (g), specific charge amount (nC / g), and moisture content (wt%) of the cellulose particles.
[0081] [Table 5]
[0082] FIG. 6 shows a drawing substitute photograph (A) showing the state of adhesion to a glass bottle in (A: normal state), a drawing substitute photograph (B) showing the state of adhesion to a glass bottle in (B: dry state), and a drawing substitute photograph (C) showing the state of adhesion to a glass bottle in (C: overhumid state) in Table 5. A: normal state is a powder of cellulose particles left in an atmosphere of 23°C and 50% humidity for 5.5 hours. B: dry state is a powder of cellulose particles left in an atmosphere of 105°C for 5.5 hours. C: overhumid state is a powder of cellulose particles left in an atmosphere of 23°C and 90% humidity for 5.5 hours. In a general environment, the moisture content of cellulose particles is about 5% to 15% by weight (depending on the temperature and humidity of the environment).
[0083] It can be seen from Table 5 and Fig. 6 that drying the cellulose particles increases their electrostatic charge and improves their adhesion to the glass surface. In particular, Fig. 6(B) shows that drying the cellulose particles improves their adhesion to the glass surface.
[0084] (Embodiment 9) As an additive, sodium tripolyphosphate (Na5P3O 10 In this case, sodium tripolyphosphate crystals are pulverized and granulated to use a powder (sodium tripolyphosphate powder). The average particle size of the sodium tripolyphosphate powder used is 10 μm to 30 μm, and the amount added is 10% by weight based on the entire powder layer.
[0085] (Embodiment 10) (overview) An example in which the adhesion of cellulose particles to a glass plate was improved by providing a coating layer on the cellulose particles is shown below. Fig. 7 is an image showing the cross-sectional structure of a cellulose particle provided with a coating layer. Fig. 7 shows a state in which the surface of a cellulose particle 201 is covered with a coating layer 202.
[0086] The coating layer 202 is made of a biodegradable material. Examples of the biodegradable material include water-soluble organic polymers having biodegradability. Examples of the water-soluble organic polymers having biodegradability include cellulose ethers, which are water-soluble celluloses. Examples of the water-soluble celluloses include nonionic cellulose ethers and hydroxypropyl methylcellulose.
[0087] In this example, the coating layer 202 is formed by coating an aqueous solution of water-soluble cellulose onto the cellulose particles 201. The thickness of the coating layer 202 after drying is in the range of 1 μm to 20 μm, preferably about 2 μm to 10 μm.
[0088] Coating methods include (1) a method in which cellulose particle powder is immersed in an aqueous solution containing a coating material and then dried to form a coating layer, and (2) a method (spray coating method) in which cellulose particles are suspended in an air current to form a fluidized bed, and an aqueous solution containing the coating material is sprayed onto the fluidized bed to adhere the coating material to the cellulose particle surface and then dried to form a coating layer.
[0089] In the spray coating method, the thickness of the coating layer can be controlled by adjusting the temperature and volume of the air flow used to form the fluidized bed, as well as the concentration of the aqueous solution containing the coating material and the spraying conditions.
[0090] (Example) Using the cellulose particles of sample A shown in Fig. 2 as a substrate, cellulose particles without a coating layer and cellulose particles with a coating layer were prepared. The coating layer was formed by spray coating an aqueous solution of water-soluble cellulose (Metolose (registered trademark) manufactured by Shin-Etsu Chemical) using a fluidized bed device MP01 manufactured by Powrex Corporation, so that the thickness of the coating layer when dried would be approximately 4 µm.
[0091] In this case, the buffer material for glass plates is composed of powder that is 100% cellulose component. In reality, impurities such as moisture are inevitably mixed in, so the buffer material for glass plates is composed of powder that is 90% by weight or more of cellulose component and the remainder is unavoidable impurity components.
[0092] (Evaluation of adhesion to glass plate) The adhesion to a glass plate of the above-mentioned cellulose particles with a coating layer, cellulose particles without a coating layer, and particles of sample C in FIG. 1 (acrylic particles) was evaluated using the test method shown in FIG.
[0093] Fig. 8 is an image diagram showing a method for measuring adhesion to a glass plate. In the method shown in Fig. 8, first, powder is scattered on a horizontal glass plate, and then the glass plate is stood vertically and impacted with a hammer. The number of powder particles adhering to the glass plate surface before and after the impact is determined by image analysis, and the powder residual rate is calculated by (total area of adhering particles after impact) / (total area of adhering particles before impact) x 100. The powder residual rate is the proportion of powder that did not fall off from the glass plate surface due to the impact.
[0094] FIG. 9 shows the measurement results of the powder residual rate for each powder on a glass plate. The horizontal axis is the hammer angle in FIG. 8. The hammer angle corresponds to the impact acceleration applied to the glass plate. The larger the hammer angle, the larger the impact acceleration applied to the glass plate. According to the findings of the present inventors, as a guideline, the impact acceleration applied to the glass plate at a hammer angle of 30° is 100G, the impact acceleration applied to the glass plate at a hammer angle of 45° is 390G, and the impact acceleration applied to the glass plate at a hammer angle of 60° is 680G. As is clear from FIG. 9, by covering the cellulose particles with a coating layer of water-soluble cellulose, the adhesion to the glass plate is greatly improved.
[0095] (Other examples of coating layers) Materials that can be used to form the coating layer include, in addition to cellulose, organic acids (adipic acid, succinic acid, citric acid), water-soluble inorganic salts (mirabite, etc.), sodium acetate (sodium salt of an organic acid), PLA (biodegradable resin), etc., as well as combinations of multiple of these materials. A method for forming a coating layer of these materials includes the spray coating method.
[0096] The spray coating method can be used regardless of whether the material to be coated is water-soluble or not. If the material is water-soluble, an aqueous solution of the material is used as the spray solution. If the material is insoluble or poorly water-soluble, a liquid in which fine powder of the material is dispersed is used as the spray solution. In this case, the particle size of the fine powder particles is 10% or less, preferably 5% or less, of the particle size of the base particle. In this case, a coating layer is formed in which many particles of the fine powder are attached to the surface of the base particle.
[0097] For example, suppose a coating layer of adipic acid is formed on cellulose particles with an average particle size of 150 μm. In this case, a coating layer of a desired thickness is formed by a spray coating method using a liquid containing adipic acid particles with an average particle size of 1 μm as the spray liquid. In this case, the surface of the cellulose particles is covered with a large number of adipic acid fine particles distributed in layers. The coating layer is formed by the large number of adipic acid fine particles distributed in layers.
[0098] The coating layer may be mainly composed of a biodegradable material, and additives may be added. Examples of additives include water-soluble inorganic salts and / or organic acids. For example, the coating layer can be formed by a spray coating method using an aqueous solution containing water-soluble cellulose and water-soluble inorganic salts as the spray liquid, or by a spray coating method using an aqueous solution containing water-soluble cellulose and organic acid particles as the spray liquid. The proportion of the biodegradable material in the coating layer is 50% by weight or more.
[0099] (Embodiment 11) A powder containing 95% by weight of cellulose particles with a coating layer and 5% by weight of adipic acid particles is used as a buffer material for glass plates. The cellulose particles used are those of sample A shown in FIG. 2. The coating layer is formed by the above-mentioned spray coating method using an aqueous solution of water-soluble cellulose (Metolose (registered trademark) manufactured by Shin-Etsu Chemical) so that the thickness of the coating layer when dried is about 5 μm. The adipic acid particles used have an average particle size of 10 μm to 30 μm. The powder is dried in an atmosphere at 105° C. for 5 hours to reduce the moisture content to 1% by weight or less.
[0100] (Embodiment 12) The coating layer is composed of fine powders of water-soluble cellulose and adipic acid. The base particles are cellulose particles with an average particle size of 150 μm. The coating layer is formed by a spray coating method using a mixture of an aqueous solution of water-soluble cellulose and adipic acid with an average particle size of 1 μm as the spray liquid. The thickness of the coating layer is approximately 5 μm. The mixture ratio of water-soluble cellulose to adipic acid is 5:1 by weight when dry. In this example, the adipic acid particles are contained in the coating layer of water-soluble cellulose.
[0101] (Embodiment 12) The coating layer is made of fine powder of organic acid. In this example, the coating layer is made of fine powder of adipic acid. The base particles are cellulose particles with an average particle size of 150 μm. The coating layer is formed by the spray coating method, and the spray liquid contains adipic acid with an average particle size of 1 μm. The thickness of the coating layer is about 5 μm. In this example, the coating layer is formed by a large number of adipic acid particles distributed in a spherical shell shape.
[0102] (Embodiment 14) The surface of cellulose particles is made hydrophobic to improve adhesion to glass plates. Hydrophobization makes it difficult for moisture to be adsorbed, and the particles become more electrostatically charged. This improves adhesion to glass plates. Here, the hydrophobization method involves treating the surface of the cellulose particles with alkali, followed by impregnation and washing with cyanuric chloride and stearylamine.
[0103] A specific example of the alkali treatment is described below. First, a surface activation treatment is performed on the cellulose particles. In this treatment, the cellulose particles are immersed in an aqueous solution of sodium acetate (0.5%, 20°C), and then the excess alkali solution is removed. Next, a hydrophobic treatment (surface fixation) is performed. In this treatment, the cellulose particles that have been subjected to the above surface activation treatment are immersed in a cyanuric chloride solution (concentration 5%, 20°C), and then washed with running water and ion washing water, and dried.
[0104] Next, stearylamine is dissolved in benzene to prepare a solution with a concentration of 0.05 mol / L, the temperature is adjusted to 30° C., and the dried cellulose particles are immersed in the solution, which is then dried to obtain alkali-treated cellulose particles.
[0105] Other methods for hydrophobizing the surface include fluorine plasma treatment and plasma treatment in a reducing atmosphere of a hydrocarbon (eg, methanol).
[0106] (others) A plurality of the exemplified additives may be used at the same time. Powders other than the exemplified additives may be added as additives. Various treatments may be performed on the powders used. The additives may be used as a solution to coat the surfaces of the cellulose particles. Examples of the coating method include the spray coating method described above. The powder layers 111 to 113 may be made of powder containing 100% cellulose components.
[0107] It is also possible to combine the use of one or more of the exemplified additives with various treatments (electrification, plasma treatment, drying treatment) for cellulose particles or the formation of a coating layer. Cellulose particles with different average particle sizes can also be mixed and used. For example, a mixture of cellulose particle powder with an average particle size of 100 μm and cellulose particle powder with an average particle size of 5 μm to 50 μm (e.g., 10 μm) is used as the cellulose particle powder.
[0108] A coating layer containing a plurality of materials is also possible. The combination of materials contained in the coating layer can be selected from the plurality of materials disclosed in this specification. The coating layer can be formed into a multi-layer structure of two or more layers. For example, a cellulose particle is covered with two coating layers. In this case, the first coating layer is a layer of water-soluble cellulose, and the second coating layer is a layer of organic acid.
[0109] According to the technology disclosed in this specification, it is possible to obtain a glass laminate that has a reduced impact on the natural environment and meets the requirements for holding glass sheets stacked together. [Explanation of symbols]
[0110] 101...glass plate, 102...glass plate, 103...glass plate, 104...glass plate, 111...powder layer, 112...powder layer, 113...powder layer, 201...cellulose particles, 202...coating layer.
Claims
1. A buffer material to be interposed between glass plates, the buffer material is a powder containing cellulose particles on which a coating layer is formed, The powder contains 50% by weight or more of a cellulose component.
2. The buffer material for glass plates according to claim 1 , wherein the coating layer contains water-soluble cellulose.
3. A buffer material to be interposed between glass plates, the buffer material is a powder containing cellulose particles, The powder contains 50% by weight or more of a cellulose component.
4. 4. The buffer material for glass plates according to claim 3, wherein the cellulose particles are granulated viscose.
5. 4. The buffer material for glass plates according to claim 3, wherein the powder contains organic acid particles having an average particle size smaller than that of the cellulose particles.
6. 6. The buffer material for glass plates according to claim 5, wherein the organic acid is one or more selected from the group consisting of adipic acid, succinic acid, and citric acid.
7. The cellulose particles have an average particle size of 100 μm to 200 μm, 7. The buffer material for glass plates according to claim 6, wherein the organic acid particles have an average particle size of 5 μm to 50 μm.
8. 4. A buffer material for glass plates according to claim 3, wherein the powder contains, as an additive, particles of a material whose average particle diameter is smaller than the average particle diameter of the cellulose particles and whose position in the triboelectric series is on the lower potential side than the cellulose particles.
9. 9. The buffer material for glass plates according to claim 8, wherein the additive is particles of a material whose position in the triboelectric series is in the negative region.
10. 4. The buffer material for glass plates according to claim 3, wherein the cellulose particles have a moisture content of 1% by weight or less.
11. 4. The buffer material for glass plates according to claim 3, wherein the powder contains a water-soluble inorganic salt.
12. The water-soluble inorganic salts include Na 2 SO 4 , NaNO 3 , Na 2 CO 3 , NaCl, KCl, NaOH, Na 2 B 4 O 7 10H 2 O, Na 5 P 3 O 10 The buffer material for glass plates according to claim 11, wherein the buffer material is one or more selected from the following:
13. 4. The buffer material for glass plates according to claim 3, wherein the powder contains sodium acetate.
14. 4. The buffer material for glass plates according to claim 3, wherein the powder contains one or more selected from the group consisting of adipic acid, succinic acid, and citric acid.
15. 4. The buffer material for glass plates according to claim 3, wherein the surfaces of the cellulose particles are covered with a biodegradable coating layer.
16. 16. The buffer material for glass plates according to claim 15, wherein the coating layer is a layer of a water-soluble high molecular weight organic polymer.
17. 17. The buffer material for glass plates according to claim 15 or 16, wherein the coating layer is a layer of water-soluble cellulose.
18. 17. The buffer material for glass plates according to claim 15 or 16, wherein the coating layer contains a water-soluble inorganic salt and / or an organic acid.
19. 4. The buffer material for glass plates according to claim 3, wherein the cellulose particles are covered with a coating layer containing a water-soluble inorganic salt.
20. 4. The buffer material for glass plates according to claim 3, wherein the cellulose particles are covered with a coating layer containing an organic acid.
21. A glass laminate in which at least two glass plates are laminated via a buffer material for glass plates, The buffer material for glass plates is a powder containing cellulose particles, The glass laminate, wherein the powder contains 50% by weight or more of a cellulose component.
Citation Information
Patent Citations
sensor
JP1991053112A
Peeling agent
JP1993294664A
Shock-absorbing spacer for sheet glasses and stacked glass sheets
WO1999033757A1
Interleavant particles for location between stacked glass sheets
WO2022148947A1
Interleaving powder
WO2022180222A1
Cited By
Solid pharmaceutical compositions
CN122768248A